Impermanence, Hybridity, Violence: Notes towards a Global Technology Studies. (March 2023) - Abraham, Itty
This short essay explores some of the issues at stake when science and technology studies (STS) are situated within a global frame. Global, in this reading, is both historical and aspirational. As historical, it rejects the East-West dichotomy, insisting instead on one world as the outcome of multiple unequal and uneven world-making processes. As aspirational, to consider what a global STS would look like this essay imagines a world where technology studies were invented in the megacities of the Global South. At once it becomes clear that familiar concepts need revision: illegibility gets added to legibility, repair and dismantling join production and construction, permanence and impermanence occupy the same register of privilege. Making particular what had been considered general forces a reconsideration of the objects, methods, boundaries and histories of our studies. This is further demonstrated by a comparison of hybridity/isation as it is understood respectively in STS and post-colonial studies. What becomes apparent is the relative absence of violence as a core STS concept, notwithstanding its centrality in the making of the modern world. Going global exposes intellectual foundations STS scholars have been unable or unwilling to acknowledge; this alone makes the exercise productive and worthwhile.